2010
DOI: 10.1021/ma100783y
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Neat Triblock Copolymers and Copolymer/Homopolymer Blends Near Network Phase Windows

Abstract: The phase behavior of poly(isoprene-b-styrene-b-methyl methacrylate) (ISM) copolymers near the styrene-rich network phase window was examined through the use of neat triblock copolymers and copolymer/homopolymer blends. Both end-block and middle-block blending protocols were employed using poly(isoprene) (PI), poly(methyl methacrylate) (PMMA), and poly(styrene) (PS) homopolymers. Blended specimens exhibited phase transformations to well-ordered nanostructures (at homopolymer loadings up to 26 vol % of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 58 publications
(150 reference statements)
11
80
1
Order By: Relevance
“…There are five common morphologies for AB diblock copolymers including body‐centered cubic spheres or close‐packed spheres (S or S cp ), hexagonally‐packed cylinders (hex), double gyroid (G), orthorhombic network (O), and lamellae (lam). In addition to morphologies in the diblock copolymer system, an alternating gyroid (G A ) is shown in the triblock copolymer system . Several reports have shown that network morphologies, such as the gyroid, exhibit superior mechanical properties relative to their one‐ (1D) and two‐dimensional (2D) counterparts (e.g., hex and lam) due to the continuity of the mechanical supporting domain .…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
“…There are five common morphologies for AB diblock copolymers including body‐centered cubic spheres or close‐packed spheres (S or S cp ), hexagonally‐packed cylinders (hex), double gyroid (G), orthorhombic network (O), and lamellae (lam). In addition to morphologies in the diblock copolymer system, an alternating gyroid (G A ) is shown in the triblock copolymer system . Several reports have shown that network morphologies, such as the gyroid, exhibit superior mechanical properties relative to their one‐ (1D) and two‐dimensional (2D) counterparts (e.g., hex and lam) due to the continuity of the mechanical supporting domain .…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
“…[17] An elegant approach to regulate the properties of block copolymers lies in blending with polymers possessing architecture similar to one of the constituent blocks. [15,[18][19][20][21][22] This allows targeting a multitude of bulk morphologies based on one single block copolymer by simply adjusting the overall blend composition, leading to optimized end-use properties. Actually, new materials with tailored features are also possible to be created through blending with elaborate design.…”
Section: Introductionmentioning
confidence: 99%
“…10 Based on polymer composition, our P(I-IS-S-SM-M) was expected to self-assemble into hexagonally-packed cylinder structures. However, our tapered triblock material was found to form an alternating gyroid (Q 214 ) network.…”
mentioning
confidence: 99%